(untitled) (Repertorio Científico, 2022)
Forest fires are a serious socio-environmental problem during the dry months on the indigenous reserves in southern Costa Rica (Talamanca mountain range). The combination of anthropic (pasture burning) and natural (decreasing precipitation, high sunshine and winds) factors generates annually optimum conditions for fires spreading the impact of which can be evaluated in intensity and range through satellite imagery. Sentinel 2 imagery, from the European’s Space Agency (ESA) programme Copernicus, has information in the mid-infrared bandwidth (from 2100 to 2280 nanometers) that maps the the extent of those forest fires with resolution of 20 meters per pixel. The use of a burning index based on the mid-infrared allowed forest fires intensity and extension to be mapped on wildfires occurred in the end of February or early March of 2020, on the Salitre and Cabagra indigenous reservations (Buenos Aires de Puntarenas, Costa Rica).